Web-based impression management? Salient features for CSR disclosure prominence. Issue 1 (6th January 2020) - Chong, Sabrina; Rahman, Asheq
Abstract : Purpose: The purpose of this paper is to identify the web-based features of corporate social responsibility (CSR) disclosure that play a role in making CSR information prominent to investors and give the information better recognition for investment decisions. Design/methodology/approach: The authors posit a positive association between the company's capital market performance and the web-based features used for CSR disclosure by the company. The authors argue that the more effective the feature is in enhancing the prominence of CSR information, the higher is the share turnover and market value of shares of a company, and the lower is its share prices' bid-ask spread. Five specific web-based features, namely, the location, accessibility, medium, variety and extent of disclosure are identified as features used for web-based CSR disclosure. The research framework is drawn from Brennan and Merkl–Davies' (2013) impression management strategies and Merton's (1987) "investor recognition hypothesis". Findings: The findings show that visual and structural emphases of CSR information via specific web-based features enhance information prominence and could favourably influence investors' impression towards the company. Investors are likely to make investment decisions in favour of the company, resulting in a higher share turnover along with increased market value of the shares of the company and lower bid-ask spread of its share prices. Research limitations/implications: The paper highlights the significance of utilisation of web-based features in enhancing CSR information prominence for impression management purposes. Practical implications: The findings have the potential to benefit preparers, users and policymakers by enhancing their knowledge and understanding of the utilisation of web-based CSR disclosure features. Specifically, preparers will be more aware of web-based feature(s) that could be useful in projecting CSR-related information to their stakeholders. Social implications: The study will help enhance the dissemination of web-based CSR information. Originality/value: The study adds to the literature on web-based CSR disclosure, by developing a structured approach to examine the effectiveness of web-based features for investors' impression management.